Outcomes in Adolescent Pregnant Patients Infected With SARS-CoV-2 [A249]. (May 2022) - Murrin, Ellen M.; Nguyen, Anh Q.; Hitchings, Laura; Nasrallah, Sebastian; Wang, Jenny; Gomez, Luis M.
Abstract : INTRODUCTION: Pregnancy carries increased risk factors for severe COVID-19 and adverse obstetric outcomes. Yet, it has not been evaluated whether increased risk during pregnancy varies with age. We sought to evaluate the risk of severity and adverse obstetric outcomes in SARS-CoV-2 positive adolescent patients compared to both non-infected adolescent and infected non-adolescent subjects. METHODS: Retrospective study across four Inova Health System Hospitals between March 2020 and January 2021. Patients were grouped by age and SARS-CoV-2 status: (i) adolescents (aged 14–19 years) SARS-CoV-2-positive, (ii) adolescents SARS-CoV-2-negative, and (iii) adults (age >20 years) SARS-CoV-2-positive. Statistical pairwise and regression analyses evaluated differences in disease distribution, severity, rates of prematurity, and cesarean delivery (CD) between group (i) and groups (ii) and (iii). RESULTS: Compared to SARS-CoV-2-negative adolescents (n=394), SARS-CoV-2-positive adolescents (n=48) were more likely to be Hispanic (91.7% versus 12.2%; adjusted P <.001), be uninsured (50% versus 7.9%; adjusted P <.001), require CD (25% versus 11.9%; adjusted P =.03), and deliver at greater gestational age (39 1/7 versus 38 4/7 weeks; adjusted P =.002). Compared to adult SARS-CoV-2-positive patients (n=695), adolescent SARS-CoV-2-positive patients were more likely to be Hispanic (91.7% versus 74.5%; adjusted P =.006), asymptomatic (79.2% versus 60.7%; adjusted P =.03), and to deliver at greater gestational age (39 1/7 versus 37 6/7 weeks; adjusted P =.004). We found no significant difference in the rates of prematurity, fetal growth restriction, NICU admission, and stillbirth. CONCLUSION: SARS-CoV-2 unequally affects Hispanic and uninsured adolescent pregnant patients. Infected adolescents are at high risk for CD compared to their non-infected adolescent counterparts. Infected pregnant adolescents tend to present with fewer COVID-19 symptoms compared to infected pregnant adults. Other obstetric outcomes were comparable among groups.